Estimating the economic impact of governance in disaster risk management: Theory and rvidence from Latin America and the Caribbean - Roberto Guerrero Compeán; Eduardo Zegarra Méndez; Sergio Lacambra Ayuso (Inter-American Development Bank (IDB), 2024)
Strengthened governance is crucial to reduce economic risks associated with disasters, but little is known about its impact. We combine a new dataset on disaster risk management governance for 26 countries from the Latin America and Caribbean region with annual information on economic losses resulting from disasters between 1980 and 2016. To account for endogenous disaster risk management (DRM) governance processes, we exploit the fact that changes in DRM regulatory frameworks affect a country's capacity for disaster risk identification and reduction to provide instrumental variable estimates of their impact. We find that disasters cause substantial economic losses and that a more robust governance for disaster risk resilience to economic losses reduces the expected economic toll caused by natures shocks. Our estimates suggest that the improvement of DRM governance in Latin America and the Caribbean mitigate the economic toll of disasters, especially in a context where climate change leads to the occurrence of more frequent and severe natural hazards across the region.
Keywords: O54; Q54; Q58; 330; disaster risk resilience; governance; economic losses; Latin America and the Caribbean